2008
DOI: 10.1210/jc.2008-0126
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of the Ki-67 Labeling Index in Growth Hormone-Secreting Pituitary Adenomas

Abstract: The Ki-67 labeling index may predict clinical outcome in postsurgical management of acromegalic patients. We suggest routine Ki-67 evaluation in GH-secreting pituitary adenomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
4
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 14 publications
5
60
4
2
Order By: Relevance
“…Previous results from our group showed that the Ki-67 is significantly higher in resistant tumours (23). The absence of adenomas with higher Ki-67 in this independent case series might account for these results.…”
Section: European Journal Of Endocrinologysupporting
confidence: 73%
See 2 more Smart Citations
“…Previous results from our group showed that the Ki-67 is significantly higher in resistant tumours (23). The absence of adenomas with higher Ki-67 in this independent case series might account for these results.…”
Section: European Journal Of Endocrinologysupporting
confidence: 73%
“…Ki-67 labelling index (LI) was evaluated, in each case, in at least five non-overlapping representative areas counting at least 1000 cells, as previously reported (23).…”
Section: Histopathological Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some novel genetic factors have been identified that predict difficult disease management in acromegaly. These newer factors, taken together with the standard pathological measures of tumor aggression such as granulation pattern, Ki-67 and gsp mutations can help to predict tumor responses to SSAs used postoperatively (Barlier et al 1998, Bhayana et al 2005, Fusco et al 2008. For instance, mutations in the aryl hydrocarbon receptor interacting protein (AIP) gene lead to a significantly more aggressive phenotype in acromegaly including younger age at onset, larger tumor size, higher hormonal levels, and a significantly poorer response to SSA in terms of hormonal reduction and tumor shrinkage (Daly et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…8,18) Various attempts have been made to establish markers that correlate with the clinical behavior of pituitary adenomas, such as invasion, recurrence, or malignancy. 1,2,5,[7][8][9][10][12][13][14][15]17,[19][20][21][22][23][24][27][28][29][30][31][32][33] Among the available methods of growth fraction determination, Ki-67 is a reliable marker for growth fraction determination of various specific cell cycle antigens. 1,12,32) Ki-67 is a protein which reacts with a …”
Section: Introductionmentioning
confidence: 99%